Exogenous Variables and their Influence on Domestic Credit Provision in Nigeria: Evidence from Quantile Regression - Veršič, Sabina (Naše gospodarstvo/Our economy, 2024)
The relevance of domestic credit to an economy has spurred interest in studies that seek to examine the factors that determine it. In this study, the focus is to evaluate the role of exogenous factors in influencing domestic credit provision in Nigeria. The study used a monthly dataset that covered the period from 2007M12 to 2024M5 under the framework of quantile regression. The findings of the study reveal that oil price had a positive and significant impact on domestic credit provision at all the quantiles, while world interest rate had a negative and significant impact on domestic credit provision at the 25th quintile. The exchange rate and bank reserves exerted a positive and significant impact on domestic credit provision at all the quantiles, while the impact of the Treasury bills rate was positive and significant only at the 25th and 50th quantiles. The study suggests that, in regulating credit provision in Nigeria, monetary authorities should closely monitor these exogenous variables as well as exchange rate movement.